Rainfall shocks and child health: the role of parental mental health. (2nd January 2021) - Trinh, Trong-Anh; Feeny, Simon; Posso, Alberto
ABSTRACT: This study examines the impacts of rainfall shocks on child health in Vietnam. It uses Young Lives data matched with province level climate data covering the period 1970–2014. Existing literature demonstrates that shocks can impact on child health by reducing household income or through the incidence of disease. This paper identifies and confirms a third mechanism: shocks impacting on parents' mental health which, in turn, reduce children's physical health. We find that one unit increase in parental mental health caused by rainfall shocks will increase the probability of a child being underweight by 0.976. Using an instrumental variable strategy, we can interpret these results as causal. We instrument parental mental health with a variable that captures whether the adult has been a victim of a crime. We also find that households that receive support, from both formal and informal channels, are less vulnerable to rainfall shocks, in terms of reducing negative health outcomes.